1989
DOI: 10.1002/esp.3290140608
|View full text |Cite
|
Sign up to set email alerts
|

Soil erosion modelling using ‘answers’ and geographical information systems

Abstract: The linkage of the model ANSWERS and a Geographical Information System to simulate surface runoff and soil erosion is described. The GIS can be used to provide (such as slope and aspect), store, change, and display data needed for simulation models. Conservation scenarios can be designed within the CIS and evaluated by the model. The results can be compared with other scenarios and displayed in the CIS.Model output is very sensitive to small changes of several input variables, such as infiltration, antecedent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(13 citation statements)
references
References 1 publication
0
12
0
1
Order By: Relevance
“…Numerous studies (e.g. Jetten et al 1999Jetten et al , 2003Tucker & Whipple 2002;Tucker 2004;Van Griensven et al 2006) applied sensitivity analysis on various erosion models such as MPSIAC (Behnam & Parehkar 2011), CREAM (Lane & Ferriera 1982), EUROSEM (Veihe & Quinton 2000), WEPP (Nearing et al 1990), PSEM-2D (Nord & Esteves 2005), USLE (Tattari & Bärlund 2001;Liu & Liu 2010), GUEST (Misra & Rose 1996), ANSWERS (De Roo et al 1989), etc. Furthermore, White and Chaubey (2005) used sensitivity analysis to identify the parameters that most influence predicted flow, sediment and nutrient outcomes for the Soil and Water Assessment Tool (SWAT) model.…”
mentioning
confidence: 99%
“…Numerous studies (e.g. Jetten et al 1999Jetten et al , 2003Tucker & Whipple 2002;Tucker 2004;Van Griensven et al 2006) applied sensitivity analysis on various erosion models such as MPSIAC (Behnam & Parehkar 2011), CREAM (Lane & Ferriera 1982), EUROSEM (Veihe & Quinton 2000), WEPP (Nearing et al 1990), PSEM-2D (Nord & Esteves 2005), USLE (Tattari & Bärlund 2001;Liu & Liu 2010), GUEST (Misra & Rose 1996), ANSWERS (De Roo et al 1989), etc. Furthermore, White and Chaubey (2005) used sensitivity analysis to identify the parameters that most influence predicted flow, sediment and nutrient outcomes for the Soil and Water Assessment Tool (SWAT) model.…”
mentioning
confidence: 99%
“…In LISEM the Manning equation is used to calculate flow velocities. Sensitivity analysis has shown that model results are very sensitive to the value of Manning's n (De Roo et al, 1989;Jetten et al, 1998). It is also questionable whether the Manning equation, which was developed for open channel flow, can be applied to shallow overland flow, where flow depths may be less than the average roughness height (Takken and Govers, 2000).…”
Section: Hydraulic Resistance Of Interrill Flowmentioning
confidence: 99%
“…These also vary considerably in terms of their purposes and both spatial and temporal scales involved, as well as their conceptual bases (De Vente and Poesen, 2005). They are usually classified by the way erosion is either physically evaluated or not, and accordingly, into empirical models (Table I) and process‐based models (De Roo et al , 1989; Almorox et al , 1994; Favis‐Mortlock et al , 1996; Mitasova and Mitas, 1998; Jetten et al , 2003).…”
Section: Introductionmentioning
confidence: 99%